(untitled) (Medical Forum Monthly, 2024)
Objective: This article focuses on the mixed perceptions of the dentists in treating patients on blood thinners and the awareness amongst them regarding protocol and management of such patients. Study Design: Cross-sectional descriptive and analytical study Place and Duration of Study: This study was conducted at Jinnah Medical and Dental College from August 2013 to December 2013. The data was collected from three dental colleges of Karachi. Material and Methods: The study was conducted at Jinnah Medical and Dental College. A 17-item questionnaire was used to collect the data. The data was collected from three dental colleges of Karachi to evaluate the dentist’s perception and protocols put into practice related to patients on blood thinners. The study included 92 dentists. The data was stored in excel worksheet and was analyzed using SPSS. Results: Amongst the 92 dental practitioners evaluated in the research 50% advised their patients to stop antiplatelet therapy prior to a dental procedure. 64.13% of the dentists where of the opinion that antiplatelet therapy be stopped before performing any treatment 94.56% of the dentists said they are aware of the reasons why patients are kept on anticoagulant drugs. Based on the data collected 67.39% of the dental practitioners delayed the treatment for patients taking blood thinners 95.65% referred the patients to their cardiologist prior to an invasive treatment. The optimal range of INR was known by 84.78% of practitioners. Conclusion: Dental practitioners in this study population display a wide range of practice in their approach to patients on blood thinners. A trend towards overly conservative management is seen in the former. In contrast, the approach to the patients appeared to be haphazard, with about 20% of those never checking the INR pre-operatively. There is a clear need for greater awareness of an evidence-based approach to the dental management of this unique patient group to avoid unnecessary and preventable complications. There is an acute need for creating awareness and adherence to the new guidelines for safe and effective practice.